Akulturasi Budaya Dalam Musik Keroncong di Indonesia - Mintargo, Wisnu (Universitas Negeri Makassar, 2017)
Keroncong music there is telling original music of Indonesia, there is also mention Portguese music, and other opinion tell result of integration betwen culture of Portuguese with Indonesia culture. Needn’t again opposes to betwen west and east culture because that chang process happened some last century.Keroncong music have dynamics in its growth is started to come people of Portuguese, colonist of Colonialism Dutch, occupying of wartime Japan army until independence of Indonesia have experienced of change from time to time. Transformation of keroncong music in its growth one of them in natural process and also influenced by situation and condition and policy of power of that moment, start from subsidy, facilities and basic facilities which supporting until taking place keroncong music. Throug method of Brosnilaw malinowski writer try to depict change of keroncong music.